2014
DOI: 10.2298/sarh1406320v
|View full text |Cite
|
Sign up to set email alerts
|

Indications for repeated enema reduction of intussusception in children

Abstract: The accuracy of ultrasound guided saline enema in intussusception reduction is high. Delay in presentation decreases success of non-operative treatment. Delayed enema reduction is important therapeutic option for intussusceptions. Surgical treatment is indicated in cases of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…In our study, 8 patients who presented with symptoms since 6-12 h showed an 87.5% success rate, 26 patients who presented with symptoms since 12-24 h showed a 92.3% success rate, and patients who presented with symptoms more than 24 h showed 50% success rate. This is statistically significant and means that symptoms which started more than 24 h have a 50% failure rate; this finding is in agreement with Vujovic et al [9]. But this proves that even patients with a longer time of symptoms have a 50% success rate as long as they are vitally stable with no signs of peritonitis.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 8 patients who presented with symptoms since 6-12 h showed an 87.5% success rate, 26 patients who presented with symptoms since 12-24 h showed a 92.3% success rate, and patients who presented with symptoms more than 24 h showed 50% success rate. This is statistically significant and means that symptoms which started more than 24 h have a 50% failure rate; this finding is in agreement with Vujovic et al [9]. But this proves that even patients with a longer time of symptoms have a 50% success rate as long as they are vitally stable with no signs of peritonitis.…”
Section: Discussionsupporting
confidence: 89%
“…Intussusception is a common cause of children requiring admission to the emergency department and can lead to bowel obstruction. Intussusception occurs when a segment of the bowel invaginates into an immediately adjacent segment, often likened to a telescope, resulting in obstruction of the bowel, ischemia, and necrosis [ 1 , 2 ]. Five types of intussusceptions are described: ileo-colic, ileo-ileo-colic, jejuno-jejunal, jejuno-ileal, and colo-colic.…”
Section: Introductionmentioning
confidence: 99%
“…The first suggests that often, the illness is preceded by an upper respiratory infection, the second that the ileocolic region has the highest concentration of lymph nodes in the mesentery, and the third that enlarged lymph nodes are often observed in patients who require surgery. Whether the enlarged Peyer patch is a reaction to the intussusception or the cause of it is unclear (18). Rare causes include polyps, submucosal lipomas, Meckel's diverticulum and duplication cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic mucosa sloughs off, leading to the heme-positive stools and subsequently to the classic "currant jelly stool" (a mixture of sloughed mucosa, blood, and mucus). If untreated, transmural gangrene and perforation of the leading edge of the intussusceptum occur (18).…”
Section: Discussionmentioning
confidence: 99%